Determination of Material Properties of Plates from Modal ESPI Measurements - Gaul, L.; Willner, Kai; Hurlebaus, S. (Proceedings of the International Modal Analysis Conference, 1999)
Fiber reinforced composites may have unknown non-isotropic properties due to the manufacturing process. Especially injection molded members tend to have orthotropic properties due to alignment of short fibers along streamlines. To obtain the stiffness parameters of such materials, a non-destructive testing method is developed. Electronic-Speckle-Pattern-Interferometry is used to determine the eigenfrequencies and eigenmodes of square sample plates and a simple analytical model of the free vibrating plate is used to identify dynamic stiffness parameters. The method is verified by testing plates with known orthotropy and by static bending tests.
UnivIS-Import:2015-04-16:Pub.1999.tech.FT.FT-TM.determ